2010
DOI: 10.1350/ijps.2010.12.4.191
|View full text |Cite
|
Sign up to set email alerts
|

Homicidal Poisoning in Japan: Offender and Crime Characteristics

Abstract: The purpose of this study was to examine empirically those who committed homicidal poisoning in Japan (N = 96). Typically, offenders were middle-aged (mean 43.2 years), had a fixed residence (99 per cent), had no criminal record (81 per cent), were employed (68 per cent), and married (56 per cent): 54 per cent of the offenders were female. The offenders could be differentiated by categorical principal component analysis (CATPCA) into two poisoning themes: 'instrumental' (N = 65) and 'expressive' (N = 31). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Landau (as cited in Smith, 2000) stressed that cross-cultural research is needed, not only to increase our knowledge on homicide from different countries but also to test Western-based theories in other cultural contexts. The expressive/instrumental dichotomy was recently reproduced in studies from different countries such as the United States (Salfati & Bateman, 2005; Sorochinski & Salfati, 2010), Belgium (Thijssen & de Ruiter, 2011), Greece (Salfati & Haratsis, 2001), Canada (Salfati & Dupont, 2006), Finland (Santtila et al, 2001) and Japan (Zaitsu, 2010). Although these studies showed that a single framework can be applicable to homicides from different countries, they also highlighted the importance of the awareness of national differences and the need to further explore how these differences may be manifested in the behaviors offenders engage in at the crime scene.…”
Section: Introductionmentioning
confidence: 90%
“…Landau (as cited in Smith, 2000) stressed that cross-cultural research is needed, not only to increase our knowledge on homicide from different countries but also to test Western-based theories in other cultural contexts. The expressive/instrumental dichotomy was recently reproduced in studies from different countries such as the United States (Salfati & Bateman, 2005; Sorochinski & Salfati, 2010), Belgium (Thijssen & de Ruiter, 2011), Greece (Salfati & Haratsis, 2001), Canada (Salfati & Dupont, 2006), Finland (Santtila et al, 2001) and Japan (Zaitsu, 2010). Although these studies showed that a single framework can be applicable to homicides from different countries, they also highlighted the importance of the awareness of national differences and the need to further explore how these differences may be manifested in the behaviors offenders engage in at the crime scene.…”
Section: Introductionmentioning
confidence: 90%
“…The selection of crime scene action variables in the current study was made based on the robust results in both Western and Eastern studies. The researches were conducted in the United States (Salfati & Bateman, 2005;Sorochinski & Salfati, 2010), Belgium (Thijssen & Ruiter, 2011), Greece (Salfati & Haratsis, 2001), Canada (Salfati & Dupont, 2006), Finland (Santtila et al, 2001), Korea (Salfati & Park, 2007;Sea & Beauregard, 2017a), and Japan (Zaitsu, 2010).…”
Section: Multivariate Logit Analysismentioning
confidence: 99%
“…Instead, studies on homicide clearly indicate that there are other profile types that fit the characteristics of various types of homicide offenders. The recurring profiles found in this study include expressive, instrumental, visionary, hedonistic, power/control, traveling, and local homicide offenders (see Hickey, 1991;Salfati & Dupont, 2006;Zaitsu, 2010).…”
Section: Discussionmentioning
confidence: 78%
“…To illustrate the variation in these profile types, we submit that expressive homicides as emotion-laden and committed to relieve the offender’s emotional distress or anger (Salfati & DuPont, 2006); instrumental homicides achieve a goal such as revenge, financial gain, or crime concealment (Zaitsu, 2010); visionary killers murder in response to voices or visions from a good or evil power; hedonistic offenders are thrill-seekers who gain satisfaction from the act of homicide; power/control offenders kill to feel power over helpless victims; traveling murderers may kill across thousands of miles; and local offenders do not leave their comfort zone (Hickey, 1991).…”
Section: Resultsmentioning
confidence: 99%